Analysis of Significant Factor from Strategic Environmental Assessment (SEA) in RPJMD to Realize Sustainable Development in Malang - Nurakhmadi, Dito Arief; Riniwati, Harsuko; Putra, Fadillah; Prasetya, Arif (Jurnal Pembangunan dan Alam Lestari, 2023)
Strategic Environmental Assessment (SEA) is one of the environmental instruments that aims to realize sustainable development. So, it is hoped that in making the Medium-Term Development Plan (RPJMD), the SEA can be compiled as the basis for its preparation. However, many regions still make SEA after preparing the RPJMD. So, this research aims to analyze the significant factors of the SEA-RPJMD, which play an essential role in creating the RPJMD with sustainable development goals. The method used in this research is MICMAC analysis. The data is obtained from secondary data. The variables in this study consisted of 5 variables, namely the carrying capacity and capacity of the environment for development (carr), estimates of environmental impacts and risks (risk), performance of ecosystem services (serv), efficiency of natural resource utilization (eff) and the level of vulnerability and capacity to adapt to climate change (climate). The results of the analysis show that the efficiency of natural resource use (eff) and estimates of environmental impacts and risks (risk) have a relationship that can affect the whole system, this has been shown from the results of the analysis, which states that these two variables are in the linkage/relay position. In addition, from the relationship of variables, estimates of environmental impacts and risks (risk) have the most significant influence on the system. It shows that estimates of environmental impacts and risks must be studied deeply to realize an insightful RPJMD for sustainable development. Keywords: Direct, Indirect, Relationship, SEA